2019
DOI: 10.1242/dev.175604
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-CATENIN modulates the axial identity of ES derived human neural crest

Abstract: WNT/β-catenin signaling is crucial for neural crest (NC) formation, yet the effects of the magnitude of the WNT signal remain ill-defined. Using a robust model of human NC formation based on human pluripotent stem cells (hPSCs), we expose that the WNT signal modulates the axial identity of NCs in a dose-dependent manner, with low WNT leading to anterior OTX + HOX − NC and high WNT leading to posterior OTX − HOX + NC. Differentiation tests of posterior NC confirm expected derivatives, including posterior-specif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 116 publications
1
36
0
Order By: Relevance
“…SOX10 is a commonly used NCC marker that is regulated by WNT signaling, and it has been shown in Xenopus to be expressed more in trunk neural crest (NC) and lesser in cranial NC [ 34 ], from which POM and CEn are derived [ 30 ]. Interestingly, the findings of Gomez et al showed that, when differentiating NC from hESCs, CHIR concentrations below 6.5 µM and above 3.5 µM yield no SOX10-positive cells [ 35 ]. Thus, the increase of the CHIR concentration from 3 µM to 4 µM in our study might give an explanation why SOX10 cells disappeared from our differentiation cultures as well.…”
Section: Discussionmentioning
confidence: 99%
“…SOX10 is a commonly used NCC marker that is regulated by WNT signaling, and it has been shown in Xenopus to be expressed more in trunk neural crest (NC) and lesser in cranial NC [ 34 ], from which POM and CEn are derived [ 30 ]. Interestingly, the findings of Gomez et al showed that, when differentiating NC from hESCs, CHIR concentrations below 6.5 µM and above 3.5 µM yield no SOX10-positive cells [ 35 ]. Thus, the increase of the CHIR concentration from 3 µM to 4 µM in our study might give an explanation why SOX10 cells disappeared from our differentiation cultures as well.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these trunk neural crest progenitors form via an intermediary neural progenitor fate, much like in vitro NMps derived from hPSCs that require a passage via pre-neural fate to acquire posterior trunk NC features progressively (Cooper et al, 2020). All human in vitro differentiation protocols that successfully generate trunk NC identities must first generate an intermediate neuromesodermal axial progenitor, drive them to a pro-neural fate, in order to form NC (Frith et al, 2018;Gomez et al, 2019;Hackland et al, 2019). Thus, the principles we have uncovered here relating the NMp transition to trunk NC in the zebrafish might be highly relevant to trunk NC in humans and may represent a general mechanism to be further explored for therapeutic approaches in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, cells at the neural plate border could be induced to regain or recapitulate some or all aspects of the pluripotency circuit. It is certainly possible to induce the neural crest cell state de novo by recombining ectoderm and intermediate neural plate ( Dickinson et al, 1995 ), treating intermediate neural plate with inducing factors ( Liem et al, 1995 ; Garcia-Castro et al, 2002 ), or treating embryonic stems cells with neural- or neural crest-inducing factors ( Rada-Iglesias et al, 2011 ; Leung et al, 2016 ; Gomez et al, 2019a , b ; Kobayashi et al, 2020 ). However, technical difficulties in directly following the expression of pluripotency factors in cells as they transition from the blastula/epiblast toward neural induction and the formation of the neural plate border has made it hard to distinguish between the persistence of pluripotent circuits in neural crest vs. the recapitulation of these circuits.…”
Section: Development Of the Neural Plate Border And The Fates And Potmentioning
confidence: 99%